Contributions to Satellite-Based Land Cover Classification, Vegetation Quantification and Grassland Monitoring in Central Asian Highlands Using Sentinel-2 and MODIS Data - Zandler, Harald; Faryabi, Sorosh Poya; Ostrowski, Stephane (Frontiers in Environmental Science, 2022)
The peripheral setting of cold drylands in Asian mountains make remote sensing tools essential for respective monitoring. However, low vegetation cover and a lack of meteorological stations lead to uncertainties in vegetation modeling, and obstructs uncovering of driving degradation factors. We therefore analyzed the importance of promising variables, including soil-adjusted indices and high-resolution snow metrics, for vegetation quantification and classification in Afghanistan’s Wakhan region using Sentinel-2 and field data with a random forest algorithm. To increase insights on remotely derived climate proxies, we incorporated a temporal correlation analysis of MODIS snow data (NDSI) compared to field measured vegetation and MODIS-NDVI anomalies. Repeated spatial cross-validation showed good performance of the classification (80%-81% overall accuracy) and foliar vegetation model (R² 0.77-0.8, RMSE 11.23-12.85). Omitting the spatial cross-validation approach led to a positive evaluation bias of 0.1 in the overall accuracy of the classification and 25% in RMSE of the cover models, demonstrating that studies not considering the spatial structure of environmental data must be treated with caution. The 500-repeated Boruta-algorithm highlighted MSACRI, MSAVI, NDVI and the short-wave infrared Band-12 as the most important variables. This indicates that, complementary to traditional indices, soil-adjusted variables and the short-wave infrared region are essential for vegetation modeling in cold grasslands. Snow variables also showed high importance but they did not improve the overall performance of the models. Single-variable models, which were restricted to areas with very low vegetation cover (< 20%), resulted in poor performance of NDVI for cover prediction and better performance of snow variables. Our temporal analysis provides evidence that snow variables are important climate proxies by showing highly significant correlations of spring snow data with MODIS-NDVI during 2001-2020 (Pearson’s R 0.68) and field measured vegetation during 2006, 2007, 2016 and 2018 (R 0.3). Strong spatial differences were visible with higher correlations in alpine grasslands (MODIS NDVI: 0.72, field data: 0.74) compared to other regions and lowest correlations in riparian grasslands. We thereby show new monitoring approaches to grassland dynamics that enable the development of sustainable management strategies, and the mitigation of threats affecting cold grasslands of Central Asia.